DEVELOPMENT OF MEDICINE BASED ON ARTIFICIAL INTELLIGENCE - Primova Holida Anorboyevna (Journals Park Publishing, 2022)
The introduction of artificial intelligence technologies in medicine is one of the main trends in the world of healthcare. AI and neural networks can fundamentally change the entire world of medicine: transform the diagnostic system, promote the development of new drugs, improve the quality of medical services in general and reduce costs
Keywords: Artificial intelligence; medicine; technology